Legal Sources of Abuse of Authority in Corruption Crimes in Indonesia - Fathur Rauzi; Irpan Suriadiata (Universitas Muhammadiyah Yogyakarta, 2024)
One manifestation of corruption that frequently arises and has a harmful effect on the government and society is the misuse of power. This study examines the legal framework in Indonesia, including Law Number 31 of 1999 and Law Number 20 of 2001, which focus on combating corruption. It also discusses the involvement of law enforcement agencies such as the Corruption Eradication Commission (KPK), the Police, and the Prosecutor's Office. This article examines the legal foundations for addressing instances of abuse of power in relation to criminal acts of corruption in Indonesia. Furthermore, this paper assesses the efficacy of implementing these laws to combat instances of authority abuse, as well as the challenges encountered in real-world scenarios. Through a comprehensive comprehension of the current legal frameworks and the obstacles encountered in their execution, it is anticipated that viable resolutions can be identified to enhance endeavors aimed at eradicating corruption in Indonesia